Analysis of Data Exit Security Review under the Background of Digital Trade: with Comments on the Chinese Measures for Data Exit Security Assessment (Draft for comments) - Liying, Zhang; Jiabao, Duan (VNU Journal of Science: Legal Studies; Vol 38 No 1DO - 10.25073/2588-1167/vnuls.4429, 2022)
Data exit brings new growth and opportunities for the development of digital trade in various countries, but without regulation, it may damage national security interests. Therefore, it is necessary to study the review rules of data exit, which is of great significance to maintain national security and ensure the development of digital trade. Therefore, under the legal basis provided by the Cybersecurity Law and the Data Security Law, China actively explored and formulated specific rules for data exit assessment, and published the Measures for Data Exit Security Assessment (Draft for comments) (hereinafter “the Measures”) in October 2021. The Measures is undoubtedly a beneficial attempt to protect national security and realize the orderly exit of data. It has made a significant breakthrough in relevant rules. However, there are still some rules to be improved. In terms of such rules in other territories, the United States and the European Union have adopted data exit review mechanisms with different value orientations, which have their own advantages and characteristics, can provide references for China to improve data exit security review rules.